4x-1=-2x+12

Simple and best practice solution for 4x-1=-2x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-1=-2x+12 equation:


Simplifying
4x + -1 = -2x + 12

Reorder the terms:
-1 + 4x = -2x + 12

Reorder the terms:
-1 + 4x = 12 + -2x

Solving
-1 + 4x = 12 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-1 + 4x + 2x = 12 + -2x + 2x

Combine like terms: 4x + 2x = 6x
-1 + 6x = 12 + -2x + 2x

Combine like terms: -2x + 2x = 0
-1 + 6x = 12 + 0
-1 + 6x = 12

Add '1' to each side of the equation.
-1 + 1 + 6x = 12 + 1

Combine like terms: -1 + 1 = 0
0 + 6x = 12 + 1
6x = 12 + 1

Combine like terms: 12 + 1 = 13
6x = 13

Divide each side by '6'.
x = 2.166666667

Simplifying
x = 2.166666667

See similar equations:

| m+1/2=5 | | 3ax-x= | | 2/3x+5/5x | | 3x+5=-10+x | | 10.35(3)(15)=a | | x^2+2/3x-26/9 | | 6/8x=72 | | 33(x+2/5)=x-1/3 | | 10.35(3)(15)=465.75 | | x^2+y^2+10x+12y+61=0 | | -4x+6=3x+-8 | | 1000/9.81 | | 52-3x=24x+16 | | 1+x^4-2x^2+1.96x^2=1.0096x^4 | | -6x+7=10-5x | | 60+.6x=.8x | | (w+8)(w-3)=0 | | 60+.6=.2 | | 5x+10=64-4x | | 5y^2+9=3y | | y^2=6y+7 | | 6x+13=35-3x | | (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x | | x^2=5+4x | | x+7=-0 | | 5+7=3x | | x^2=y^4-77 |

Equations solver categories